ANALYSIS OF CONTENT MANAGEMENT SYSTEM DEVELOPMENT FOR TAMAN MINI ONLINE TICKETING LANDING PAGE - Sahid Triambudhi; Ihsan Doni Irawan; Faisal Yusuf Fadhilah (Jurnal Riset Informatika, 2025)
Taman Mini Indonesia Indah (TMII), an iconic Indonesian cultural theme park focusing on education and recreation, exhibits high promotional and event dynamics post-revitalization, necessitating its online ticket sales landing page (tiket.tamanmini.com) to present updated information rapidly. Despite having an efficient booking system for transaction management, TMII's main landing page faces a serious operational constraint: every addition of a new ticket (ticket ID), modification, or creation of a new menu section must be executed via manual source code modification (hard code). This practice causes significant inefficiency, delays in publishing promotional tickets (e.g., school holiday bundles), and high risks of errors, directly impacting business revenue potential. This research aims to conduct a comprehensive needs analysis for designing a dedicated Content Management System (CMS) module for TMII's ticket sales landing page, thereby eliminating the reliance on hard coding. The methodology employed is qualitative descriptive, using observation and interviews with the website and operational management teams for data collection. The primary result of this analysis is a detailed specification of the functional and non-functional requirements for the CMS module, including independent CRUD (Create, Read, Update, Delete) capabilities for tickets and banners. The CMS design is expected to significantly enhance the operational efficiency of the management team, ensure content accuracy, and accelerate business response to market opportunities, ultimately making content management for online tickets independent and efficient.